PROBLEMS FACED BY SMALL SCALE INDUSTRIES ON ADOPTION OF HRD PRACTICES - WITH SPECIAL REFERENCE TO TIRUNELVELI DISTRICT, TAMIL NADU - Kumar, V. Praveen; Ani, J. Jeya (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines the challenges faced by small-scale industries (SSIs) in adopting Human Resource Development (HRD) practices, with a specific focus on Tirunelveli District, Tamil Nadu. SSIs play a pivotal role in regional economic development, but their ability to implement modern HRD practices is often constrained by multiple factors. Key issues include limited financial resources, lack of awareness, inadequate training facilities, resistance to change, and a shortage of skilled HR professionals. These challenges prevent SSIs from improving employee skills, enhancing productivity, and achieving sustainable growth. The research uses a combination of quantitative and qualitative methods to assess the impact of these challenges on the overall growth and competitiveness of SSIs in the region. The findings reveal that financial constraints and lack of awareness are the most significant barriers, while other factors such as low literacy levels and limited external support also play a role. The study concludes with recommendations to address these issues, offering potential solutions to improve HRD adoption, thereby enhancing the performance and sustainability of SSIs in Tirunelveli. This research contributes to understanding the critical HRD needs of SSIs and provides insights for policymakers and industry leaders to help overcome these challenges.